(536) مجموعة القوانين والقرارات التي صدرت في الفترة من يناير إلى يوليو 1976 Collection of laws and resolutions issued between January and July 1976 - آمال حسن الحريري (معهد التخطيط القومي, 2026)
المذكرة عبارة عن سجل توثيقي شامل للقوانين والقرارات الجمهورية والوزارية الصادرة خلال النصف الأول من ذلك العام. تتسم المادة العلمية بالتنوع الكبير، حيث تغطي جوانب إدارية وتشريعية مست مختلف قطاعات الدولة، بدءاً من تنظيم الأجور والعلاوات وبدلات الانتقال، وصولاً إلى شئون الإدارة المحلية والجمارك والإعلام. كما يبرز الملف الجانب التنظيمي لقطاعات الإنتاج الحيوي كالبترول والصناعة، مع التركيز على وضع مواصفات قياسية للإنتاج المحلي، مما يعكس الرغبة في ضبط الأداء المؤسسي والخدمي في تلك الفترة. وتسلط الضوء على التوجهات الاقتصادية لمصر في منتصف السبعينيات، من خلال رصد اتفاقيات التعاون الفني والمالي مع دول عدة مثل العراق وإسبانيا وفرنسا وبريطانيا، والترخيص بتأسيس بنوك وشركات استثمارية مشتركة. كما يوثق القرارات المتعلقة بتطوير البنية التحتية والتعليمية، مثل إنشاء كليات ومعاهد فنية جديدة في المحافظات، وتنظيم الاتفاقيات الخاصة بتطوير السكك الحديدية وكهربة الريف. وبذلك، يقدم الملف صورة بانورامية للتحولات التشريعية التي واكبت خطط التنمية الاقتصادية والاجتماعية وسعي الدولة لتعزيز انفتاحها الاقتصادي وتنظيم علاقاتها الدولية. The memorandum is a comprehensive record of laws and presidential and ministerial decrees issued during the first half of that year. The material is remarkably diverse, covering administrative and legislative aspects affecting various sectors of the state, from regulating wages, allowances, and transportation stipends to local administration, customs, and media affairs. The document also highlights the regulatory aspects of vital production sectors such as petroleum and industry, with a focus on establishing standard specifications for local production, reflecting the desire to improve institutional and service performance during that period. It sheds light on Egypt's economic trends in the mid-1970s by documenting technical and financial cooperation agreements with several countries, including Iraq, Spain, France, and Britain, and the licensing of joint banks and investment companies. Furthermore, it documents decisions related to infrastructure and educational development, such as the establishment of new technical colleges and institutes in the governorates, and the regulation of agreements for railway development and rural electrification. Thus, the document presents a panoramic view of the legislative transformations that accompanied economic and social development plans and the state's efforts to enhance its economic openness and regulate its international relations.